Mathematical statistics with applications in R - Ramachandran, K. M.; Tsokos, Chris P. (Academic Press, imprint of Elsevier, 2015)
Mathematical Statistics with Applications, Second Edition, gives an up-to-date introduction to the theory of statistics with a wealth of real-world applications that will help students approach statistical problem solving in a logical manner. The book introduces many modern statistical computational and simulation concepts that are not covered in other texts; such as the Jackknife, bootstrap methods, the EM algorithms, and Markov chain Monte Carlo (MCMC) methods such as the Metropolis algorithm, Metropolis-Hastings algorithm and the Gibbs sampler. Goodness of fit methods are included to identify the probability distribution that characterizes the probabilistic behavior or a given set of data. Engineering students, especially, will find these methods to be very important in their studies.- Resumé vydavatel
Keywords: matematická statistika; R (programovací jazyk); mathematical statistics; R (computer program language); elektronické knihy; příručky; electronic books; handbooks and manuals